(untitled) (Architecture Image Studies, 2025)
This study examines the strategic role of the TNI Manunggal Membangun Desa (TMMD) Program as an instrument of Military Operations Other Than War in supporting community development in Indonesia and proposes a strategic policy framework to optimize its implementation. Grounded in post-reform civil–military relations, the study situates TMMD within the broader transformation of the Indonesian National Armed Forces from a conventional defense-oriented institution toward a multidimensional actor contributing to rural development, humanitarian assistance, and social stability. Employing a qualitative case study approach, data were collected through in-depth interviews with military and civilian stakeholders, document analysis, and field observations, and analyzed using Robert K. Yin’s qualitative data analysis framework. The findings reveal that TMMD has generated significant physical, social, and emergency-response benefits at the village level and enjoys strong public trust due to its participatory and context-sensitive implementation. However, its effectiveness remains constrained by rigid organizational structures, hierarchical decision-making, cultural resistance to civilian oversight, and regulatory ambiguity. From the perspectives of New Public Management, Transformational Leadership, and Public Value Governance, the study highlights the need for performance-based accountability, decentralized authority, transformational leadership at the territorial level, and collaborative governance mechanisms to ensure democratic legitimacy and sustainable public value creation. The study concludes that optimizing TMMD requires an integrated strategic policy framework that aligns military professionalism with community empowerment, strengthens cross-sector collaboration, and clarifies legal boundaries between military and civilian roles. Such a framework positions TMMD as a strategic, accountable, and adaptive development policy instrument capable of supporting inclusive and sustainable rural development in Indonesia.